The Kaleidoscope Model, a practical framework for analyzing food security policy change - CGIAR Research Program on Policies, Institutions, and Markets (2019)
USAID's Bureau for Food Security has integrated the Kaleidoscope Model into several training events, and IFPRI researchers are regularly invited to present the tool and engage in interactive exercises with USAID's mission staff.